Effective Complex Properties for Three-Phase Elastic Fiber-Reinforced Composites with Different Unit Cells - Sabina, Federico J.; Camacho Montes, Hector; Espinosa Almeyda, Yoanh; Guinovart Díaz, Raúl; Rodríguez Ramos, Reinaldo (2021)
The development of micromechanical models to predict the effective properties of multi-phase composites is important for the design and optimization of new materials, as well as to improve our understanding about the structure–properties relationship. In this work, the two-scale asymptotic homogenization method (AHM) is implemented to calculate the out-of-plane effective complex-value properties of periodic three-phase elastic fiber-reinforced composites (FRCs) with parallelogram unit cells. Matrix and inclusions materials have complex-valued properties. Closed analytical expressions for the local problems and the out-of-plane shear effective coefficients are given. The solution of the homogenized local problems is found using potential theory. Numerical results are reported and comparisons with data reported in the literature are shown. Good agreements are obtained. In addition, the effects of fiber volume fractions and spatial fiber distribution on the complex effective elastic properties are analyzed. An analysis of the shear effective properties enhancement is also studied for three-phase FRCs.